Effects of cilostazol treatment for patients with aneurysmal subarachnoid hemorrhage: A meta-analysis of 14 studies. (May 2022) - Li, Lian; Fu, Xiaofeng; Qiu, Huiming; Shi, Peihong
Highlights: Fourteen studies were pooled to evaluate effects of cilostazol for aneurysmal SAH. Cilostazol effectively prevents cerebral vasospasm after aneurysmal SAH. Cilostazol improves neurological functions of aneurysmal SAH patients. Cilostazol did not induce additional risk of adverse events. Abstract: Objective: To perform an updated meta-analysis to comprehensively assess the efficacy and safety of cilostazol in preventing aneurysmal subarachnoid hemorrhage (SAH)-related secondary complications. Methods: Electronic databases of PubMed, the Cochrane library, CNKI and Wanfang were searched on August 2021. Pooled odds ratio (OR) and standardized mean difference (SMD) were calculated for dichotomous and continuous outcomes, respectively. Results: A total of 14 studies [comprising 18, 726 aneurysmal SAH patients (6654 in the cilostazol group and 12, 072 in the control group)] performed in Japan or China were included. Compared with the control group, cilostazol treatment significantly reduced the median cerebral artery (SMD = −0.49; p < 0.001), improved the therapeutic efficacy (OR = 2.37; p = 0.009), decreased the incidence of symptomatic vasospasm/delayed cerebral ischemia (OR = 0.42; p < 0.001), severe angiographic vasospasm (OR = 0.54; p < 0.001), new cerebral infarction (OR = 0.33; p < 0.001), poor outcomes (OR = 0.86; p = 0.001), mortality (OR = 0.62; p < 0.001) and increased the incidence of no or mild angiographic vasospasm (OR = 1.94; p = 0.004), but did not induce more adverse events (OR = 1.08; p = 0.871). The mechanism of cilostazol treatment was to inhibit the production of tenascin-C (SMD = −1.46; p < 0.001). These results were hardly changed by subgroup analysis. Conclusion: This meta-analysis indicates cilostazol may be an effective and safe drug for aneurysmal SAH patients. However, further trials involving other world populations are required to demonstrate the generalization of treatment effects of cilostazol.